1998
DOI: 10.1073/pnas.95.10.5700
|View full text |Cite
|
Sign up to set email alerts
|

The mosquitoAnopheles stephensilimits malaria parasite development with inducible synthesis of nitric oxide

Abstract: We have discovered that the mosquito Anopheles stephensi, a natural vector of human malaria, limits parasite development with inducible synthesis of nitric oxide (NO). Elevated expression of A. stephensi NO synthase (NOS), which is highly homologous to characterized NOS genes, was detected in the midgut and carcass soon after invasion of the midgut by Plasmodium. Early induction is likely primed by bacterial growth in the blood meal. Later increases in A. stephensi NOS expression and enzyme activity occurred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
392
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 379 publications
(410 citation statements)
references
References 39 publications
17
392
0
1
Order By: Relevance
“…The induction of AsPrx-4783 at 7 days pBM suggests a role at extended times postdigestion. Consistent with such a role, we observed that AsNOS is induced in the midguts of blood-fed insects relative to nonfed insects at 6 and 9 days pBM and that nitrate/nitrite levels in circulating hemolymph are elevated at 7 days pBM and then gradually decrease in uninfected insects through 14 days pBM [15]. Thus, elevated AsPrx-4783 would be available to protect against ROS and RNOS generated during and after blood digestion.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The induction of AsPrx-4783 at 7 days pBM suggests a role at extended times postdigestion. Consistent with such a role, we observed that AsNOS is induced in the midguts of blood-fed insects relative to nonfed insects at 6 and 9 days pBM and that nitrate/nitrite levels in circulating hemolymph are elevated at 7 days pBM and then gradually decrease in uninfected insects through 14 days pBM [15]. Thus, elevated AsPrx-4783 would be available to protect against ROS and RNOS generated during and after blood digestion.…”
Section: Discussionsupporting
confidence: 74%
“…We also demonstrated that AsNOS catalytic activity leads to an increase in midgut nitrosative stress [15][16][17]. Our data indicate that inflammatory levels of midgut RNOS limit or inhibit parasite growth [15,17]. These RNOS, however, also impose stress on the mosquito host (reviewed in [18]).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 60%
See 2 more Smart Citations
“…infection [1,2]. Parasite development in the mosquito begins with the ingestion of blood containing sexual-stage gametocytes.…”
Section: Introductionmentioning
confidence: 99%